2003
DOI: 10.1021/op034089f
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Supersaturated Drug Solution

Abstract: In this contribution we present two cases of phase transitions, in which the ability to control the reproducible formation of the desired physical form requires a control of crystallization parameters and a deep understanding of the phase diagram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(153 citation statements)
references
References 31 publications
(39 reference statements)
7
144
0
Order By: Relevance
“…This phenomenon has been reported to occur for a number of organic compounds (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). L-L phase separation will always occur if the compound is above its melting point, or there is no crystalline form and the L-L miscibility point is exceeded.…”
Section: Discussionmentioning
confidence: 94%
“…This phenomenon has been reported to occur for a number of organic compounds (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). L-L phase separation will always occur if the compound is above its melting point, or there is no crystalline form and the L-L miscibility point is exceeded.…”
Section: Discussionmentioning
confidence: 94%
“…[103][104][105] The kinetics of polymorphic phase transformations in drug solutions have been studied in situ using a quiescent thermostated batch crystallizer placed under an optical microscope by Veesler et al. 106 While the spatial resolution of optical microscopy is limited by the wavelength of light, it offers the ability to image growth processes in situ at the length scale equivalent to that of crystal faces.…”
Section: Methodsmentioning
confidence: 99%
“…In the cases of lysozyme and BPTI, the metastable liquid phase impedes the nucleation of the solid phase, which was also observed for some organic molecules. 44,45 Note that recently, in an extremely interesting paper from Vivarès et al 46 on the crystallization of glucose isomerase in the presence of a metastable LLPS observed by confocal scanning fluorescence microscopy, it has been shown that nucleation and crystal growth mainly occurred inside the dense phase. Finally, we propose the following practical rule for crystallization: when we observe a demixion, it is bound to be metastable with respect to crystallization and therefore the best crystallization temperature is T, with T e > T g T L-L , where T e is the crystal-liquid equilibrium temperature.…”
Section: Bpti Nucleation and Llpsmentioning
confidence: 99%
“…BPTI solutions were placed in a 100-µL quiescent glass vessel inserted in a thermostated cell under an optical microscope (Nikon Diaphot) and the droplet temperature equilibrium was measured. 45 Last, BPTI solutions at initial temperatures well above the coexistence curve were rapidly quenched to a temperature below their cloud points. Phase separation rapidly occurred and the solutions underwent a macroscopic gravitydriven separation into two coexisting phases.…”
Section: (C T)mentioning
confidence: 99%